Pengembangan Sistem Deteksi God Class dan Brain Class Code Smell - Kevin Azwega; Adam Hendra Brata; Eriq Muhammad Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Code smell is defect code in object-oriented programming it can cause a problem in the maintenance software system. Defect code cause class that tends to centralize the intelligence of the software system it means god class and brain class code smells. God class occurs because of functional complexity in class high, cohesion class high, and to many use data from the other class. Brain class occurs because it has a brain method in a software system. Detection code smell can be done manually, but it has a long time if detection hundreds code in a software system. That be required tool for detection god class and brain class code smells automatically. to reduce programmer effort in overcoming god class and brain class code smells problem. This system uses software metrics to measure classification god class and brain class. This system has been tested by unit test it used whitebox method, integration testing used bottom up integration method and validation testing used blackbox method. This system can be operated detection god class and brain class code smell less than one second and have detection accuracy one hundred percent.